Potentiality of the porous geopolymer sphere in adsorption of Pb (II) from aqueous solutions: Behaviors and mechanisms. Issue 1 (1st January 2023) - Lu, Meng; Chen, Yuchi; Chen, Si; Liu, Jinxing; Mei, Meng; Wang, Teng; Li, Jinping
Abstract: In this study, a porous geopolymer sphere (PGS) was developed that comprised a mixture of coal gasification fly ash, steel slag, metakaolin and an alkaline activator (SiO2 /Na2 O molar ratio = 1.33) (44.89 wt%, 20.10 wt%, 2.01 wt% and 33 wt%) using an 8.5 wt% hydrogen peroxide foaming agent. The micro characteristics of the PGS were tested using X-ray CT, BET, XRD, and FT-TR. The mechanism to Pb adsorption was revealed via adsorption isotherm, adsorption kinetics, thermodynamics, and adsorbent characterization. Results indicated that the PGS was a mesoporous structure (the most accessible pore sizes was 9.31 nm) and the main crystalline phases in the PGS were ZK-5 zeolite, vaterite, calcium silicate, and wustite. Batch experiments showed that the adsorption of Pb by the PGS was best described by pseudo-second-order kinetics and the Langmuir isotherm model, indicating that the adsorption process was dominated by chemical adsorption. Moreover, the maximum adsorption capacity of the PGS could reach 59.31 mg/g. The mechanism of Pb(II) adsorption using the PGS mainly involves: (1) ion exchange, (2) a complexation reaction between Pb and the PGS, (3) lattice immobilization of Pb and in the ZK-5 zeolite and zeolite-like phase, (4) physical adsorption by the PGS.